Development Of A Fuzzy Reliability Centered Maintenance (Fuzzy-Rcm) Based Maintenance Strategy For Production Machines At Pt Kimia Farma Tbk, Banjaran Plant - Mochamad Ridwan Nugaraha; Didit Damur Rohman (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research was conducted at PT Kimia Farma Plant Banjaran, a pharmaceutical manufacturer producing various types of medicines. The relatively high frequency of machine failures has become a serious issue that disrupts the production process and reduces productivity. Currently, the company employs a System Corrective and Planned Maintenance method carried out once a month depending on the type of machine. However, this approach is less effective, as it still results in high downtime, unexpected maintenance costs, and potential secondary damage. This study discusses the maintenance strategy for the Blistering Machine using the Fuzzy Reliability Centered Maintenance approach. The maintenance strategy is determined based on the risk level of each machine component. Components with Very Low Risk are maintained using the Run to Failure or simple routine monitoring strategy. Low Risk components are handled through periodic Preventive Maintenance. Medium Risk components are managed using Predictive Maintenance through actual condition monitoring. Components of High Risk are managed through Condition-Based Maintenance supported by real-time data without interrupting operations. Meanwhile, components with Very High Risk require Immediate Action supported by a Failure Mode and Effect Analysis. This approach enables a more effective and efficient maintenance system that minimizes the potential for machine failures.